A Two-Band Algorithm for Total Suspended Solid Concentration Mapping Using THEOS Data - Lim, H.S.; MatJafri, M.Z.; Abdullah, K.; Asadpour, R. (Journal of coastal research, 2013)
Lim, H.S.; MatJafri, M.Z.; Abdullah, K., and Asadpour, R., 2013. A two-band algorithm for total suspended solid concentration mapping using THEOS data. Environmental monitoring through the method of traditional ship sampling is time consuming and requires a high survey cost. This study was carried out to investigate the relationship between total suspended solids (TSS) and satellite THEOS data by using a calibrated algorithm. The study area is the seawater region around Penang Island, Malaysia. Water-quality TSS values were collected simultaneously during the acquisition of the satellite imagery and later analyzed in the laboratory. The digital numbers of the corresponding TSS measurements were extracted and converted into reflectance values for algorithm regression. The two-band algorithm used here is based on the reflectance model, which is a function of the inherent optical properties of water, and this in turn can be related to the concentration of its constituents. The developed algorithm was used to correlate the digital signal and the TSS values. The generated algorithm was developed for two visible wavelengths, red and blue for this study. The digital numbers corresponding to the sea truth locations were extracted for algorithm calibration. Based on the values of the correlation coefficient squares (R2) and root-mean-square deviation (RMS), the proposed algorithm is considered superior. A water-quality image was generated using the multispectral data set and the proposed calibrated TSS algorithm. Finally, the generated TSS map was geometrically corrected to produce a geocoded map. Filtering was performed to the generated map to remove random noise, and it was color-coded for visual interpretation. This study indicates that the TSS algorithm developed from optical properties is a promising TSS model for high-accuracy TSS mapping using satellite data.